ARTIFICIAL INTELLIGENCE AND THE LAW: AN OVERVIEW - Olubiyi, Ifeoluwa A.; Rahamat Oyedeji-Oduyale; Damilola M.Adeniyi (ABUAD Law Journal, 2024)
AI has been deployed in finance, health care, law enforcement, research, teaching, communication and even transportation. In the legal industry, AI has been useful to law students, lawyers and judges. The widespread use of AI has raised salient questions over its effects on legal concepts like human rights, intellectual property, labour and employment law, criminal law, health law and entertainment law. The need for formal regulation became more evident in recent years with the popularisation of generative AI models which have brought AI closer to the people more than ever. Regulating AI is essential to curb its adverse effects on the society. It is critical that harmonised rules and policies are made across countries, to truly harness the potential of AI in enhancing socio-economic development and mitigate the risks that are inherent in the deployment of AI. This paper serves as an overview of the relationship and impact of AI in various fields of law and provides suggestions on various thorny issues raised by the deployment of AI in law.